Wounded Warrior Rescuing Thakur Ram from Deadly Epidemic - Karn, Sajan Kumar (Academic Voices: A Multidisciplinary Journal, 2011)
Educational institutions are considered change agents for they are shouldered with the responsibility of transforming individuals, society, nation and also the world. Nevertheless, what happens if the change agents themselves do not conform to the changes has been well said by Wilson in the above quote. There is no doubt to the fact that education around the globe has undergone sea changes in perspectives and practices both but Thakur Ram Multiple Campus, Birgunj, one of the biggest educational foundations in the country that had its name and fame for the academic brilliance in the times of yore, feels to be driving the same bullock carts while sports cars are being rolled down around the globe. In this composition, I have endeavored to unveil those orthodox practices, as I have perceived, against the backdrop of the breaking educational paradigms and propose to deconstruct conformist prototypes to prevent it from being more infamous. Keywords Digital literacy, banking education, subversive, paradigm, critical thinking DOI: http://dx.doi.org/10.3126/av.v1i0.5313 Academic Voices 2011; 1: 61-70